Pengaruh Wabah Penyakit Covid-19 Terhadap Minat Belajar Siswa Kelas X MAN 1 Langkat - Anita Sary, Yusuf Abdullah, Abdul Halim (Education Achievement: Journal of Science and Research, 2022)
The type of research used is quantitative research with a correlational approach. The population studied were all class X MAN 1 Langkat. The samples studied were two classes totaling 72 students. Data collection techniques using a questionnaire. The technique used to analyze the data is correlation test and simple linear regression test. The results of the study show that the trend of the covid-19 disease outbreak in some (61.1%) is high, and (38.9%) is in the medium category. So it can be concluded that the covid-19 disease outbreak variable is in the high category (61.1%). And the tendency of students' interest in learning in some (66.7%) is high, and (33.3%) is in the medium category. So it can be concluded that the variable of student interest in learning is in the high category (66.7%). The results of the simple linear regression test show that the correlation coefficient rxy is positive (0.213). From the t-test, the results of the t-count calculation are 1.971 with t-table (db = 70 ) which is 1.9944 with a significant level of 5%. So tcount < ttable then Ha is rejected and H0 is accepted. In other words, reject the alternative hypothesis (Ha) and accept the null hypothesis (H0) for testing both variables. So it can be concluded that the variable X has no effect on the variable Y.